Trends and Directions in Online Learning Research in Physics and Astronomy Education: A Bibliometric Analysis - Ishmah Luthfiyah (Universal Education, 2025)
This study aims to explore the trends and directions in online learning research within the fields of physics and astronomy, with a specific focus on how these disciplines have integrated online learning technologies. Given the rapid advancement in information and communication technologies (ICT), online learning has significantly reshaped education by overcoming traditional constraints of time and geography. This research addresses key questions about the evolution of online learning in these complex subjects, investigating the impact of various educational tools such as simulations, augmented reality (AR), and virtual reality (VR), and identifying the challenges associated with access to technology and digital literacy. To analyze the trends in this field, a bibliometric approach was employed. Data was obtained from the Scopus database, focusing on articles related to